Right-Wing YouTube: A Supply and Demand Perspective. (January 2022) - Munger, Kevin; Phillips, Joseph
YouTube is the most used social network in the United States and the only major platform that is more popular among right-leaning users. We propose the "Supply and Demand" framework for analyzing politics on YouTube, with an eye toward understanding dynamics among right-wing video producers and consumers. We discuss a number of novel technological affordances of YouTube as a platform and as a collection of videos, and how each might drive supply of or demand for extreme content. We then provide large-scale longitudinal descriptive information about the supply of and demand for conservative political content on YouTube. We demonstrate that viewership of far-right videos peaked in 2017.